2020
DOI: 10.1038/s41467-020-20010-9
|View full text |Cite
|
Sign up to set email alerts
|

A conserved regulator controls asexual sporulation in the fungal pathogen Candida albicans

Abstract: Transcription factor Rme1 is conserved among ascomycetes and regulates meiosis and pseudohyphal growth in Saccharomyces cerevisiae. The genome of the meiosis-defective pathogen Candida albicans encodes an Rme1 homolog that is part of a transcriptional circuitry controlling hyphal growth. Here, we use chromatin immunoprecipitation and genome-wide expression analyses to study a possible role of Rme1 in C. albicans morphogenesis. We find that Rme1 binds upstream and activates the expression of genes that are upre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…The fluorescent signal was not observed on hyphal cells, consistent with the presence of chitosan specifically in the chlamydospore wall. Similar staining of C. albicans chlamydospores with Eosin Y has recently been reported ( 45 ).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The fluorescent signal was not observed on hyphal cells, consistent with the presence of chitosan specifically in the chlamydospore wall. Similar staining of C. albicans chlamydospores with Eosin Y has recently been reported ( 45 ).…”
Section: Resultssupporting
confidence: 84%
“…In S. cerevisiae , the Srt1 and Rrt8/Lds1/Lds2 proteins are localized to lipid droplets, and lipid droplets are associated with the forming spore wall, suggesting some connection between lipid droplets and the assembly of the outer spore wall layers ( 34 36 ). C. albicans chlamydospores are reported to be rich in neutral lipids and lipid droplets based on both biochemical fractionation and staining with a lipid droplet dye ( 45 , 54 ). To examine lipid droplets in C. dubliniensis chlamydospores, the cells were stained with the lipid droplet dye monodansylpentane (MDH) ( 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…An overexpression study of RME1 , a zinc finger transcription factor identified its role during C. albicans chlamydospore formation. Indeed, overexpression of RME1 led to the up‐regulation of chlamydospore‐related genes, and to the binding of a TAP‐tagged Rme1 at the promoters of these target genes (Hernandez‐Cervantes et al., 2020 ). Subsequent examination of the phenotype of the overexpressing strain in chlamydospore‐inducing conditions confirmed Rme1 involvement in the process, allowing a bypass of environmental cues and regulators that are required for chlamydospore formation (Hernandez‐Cervantes et al., 2020 ).…”
Section: Overexpression Studies To Understand C Albicans ...mentioning
confidence: 99%
“…Indeed, overexpression of RME1 led to the up‐regulation of chlamydospore‐related genes, and to the binding of a TAP‐tagged Rme1 at the promoters of these target genes (Hernandez‐Cervantes et al., 2020 ). Subsequent examination of the phenotype of the overexpressing strain in chlamydospore‐inducing conditions confirmed Rme1 involvement in the process, allowing a bypass of environmental cues and regulators that are required for chlamydospore formation (Hernandez‐Cervantes et al., 2020 ). As in the previous study, the knockout mutant showed the opposite phenotype, that is, the absence of chlamydospore formation, even in favorable conditions.…”
Section: Overexpression Studies To Understand C Albicans ...mentioning
confidence: 99%
“…However, environmental factors, including nutrients, are also key regulators for development and reproduction in many fungi. Genes regulating sporulation are known to affect some SMCs ( 48 51 ). Therefore, investigation of the expression of SMCs across fungal development in additional environmental contexts provides an opportunity to enhance our understanding of their regulation and function.…”
Section: Introductionmentioning
confidence: 99%